PENERAPAN PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Dhika Maretasani, Laurensia (Widya Warta, 2018)
The study aimed to: (1) test and analyze the learning completenesst of student’s mathematical problem solving ability in PBL, (2) know student’s mathematical problem solving ability in PBL more than student’s mathematical problem solving ability in conventional learning, and (3) know the improvement of student’s mathematical problem solving ability  in PBL. The research design was quasi experimental with nonrandomized control group, pretest-postest design. The population of this study were all of students of SMA Negeri 1 Gondang (Senior High School) sitting in the 10th grade. The sampling technique was purposive sampling; selected XH were as a control group and XA as experimental group. The data were obtained with the test method. Sample groups were pretested and posted with the same instruments. The conclusions are: (1) the mathematical problem solving ability of the students in PBL reaches completeness  (87.5%) with a return limit of 75%; (2) student's mathematical problem solving ability in PBL (average 75.39) is better tthan student’s mathematical problem solving ability in conventional learning (average 69.62); and (3) student’s mathematical problem solving ability in PBL increases by 0.67 (medium).